The roots of the equation are `alpha` and`beta` . `alpha - beta = 1`

`alpha - beta= 1` or `alpha = 1 + beta`

From the roots of the equation we get `(x - alpha)(x - beta) = 0`

`5x^2 - px + 1 = 0 => x^2 - (p/5)*x...

## View

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The roots of the equation are `alpha` and`beta` . `alpha - beta = 1`

`alpha - beta= 1` or `alpha = 1 + beta`

From the roots of the equation we get `(x - alpha)(x - beta) = 0`

`5x^2 - px + 1 = 0 => x^2 - (p/5)*x + (1/5) = 0`

=> `x^2 - (alpha + beta)*x + alpha*beta = x^2 - (p/5)*x + (1/5)`

This gives `alpha*beta = 1/5 and alpha + beta = p/5`

=> `(1 + beta)*beta = 1/5 and 1 + beta + beta = p/5`

=> `5*beta^2 + 5*beta - 1 = 0`

=> `beta = (-3*sqrt5 - 5)/10 and beta = (-3*sqrt 5 + 5)/10`

`1 + 2*beta = p/5`

=> p = `1 + (5*2*(-3*sqrt5 - 5))/10`

=> p = `-3*sqrt 5 - 4`

or p = `1 + (5*2(-3*sqrt 5 + 5))/10`

=> p = `-3*sqrt 5 + 6`

**The value of p can be** `-3*sqrt 5 - 4 and -3*sqrt 5 + 6`